Analysis of the development of COVID-19 epidemic in different countries using the fractional differential model of infection spread - Efimova, Taisia A.; Timoshchenko, Igor A.; Hliatsevich, Maryna A. (Journal of the Belarusian State University. Physics, 2024)
The evolution of the COVID-19 epidemic in 100 countries of the world was analysed using the infection spread model based on the use of fractional calculus. It was shown that the developed model allows one to adequately reproduce the dynamics of the number of deaths and the number of new cases of infection in all studied states. It has been established that, according to the main characteristics of the epidemic spread, the countries under consideration can be distributed into three clusters, each of which is characterised by its socio-demographic composition of the population and the level of economic development. Identification of such clusters in the future can lead to a more optimal and rapid search for model parameters that will be used to reproduction and predict the development of infections similar in distribution pattern to the COVID-19 infection. To describe the second and subsequent waves of the epidemic, a modification of the model has been proposed. This modification includes an additional equation that accounts the presence of individuals infected with the virus, but who are not conatgious. It was shown that with each subsequent wave of the epidemic, the order of the fractional derivative, which makes it possible to achieve the best fit to statistical data, tends to unity. It can be hypothesized that this fact is a reflection of the increasing number of new strains of the virus circulating in the population.